INSECTICIDAL JOINT ACTION OF TERNARY EXTRACT MIXTURES OF FOUR SPECIES OF TROPICAL PLANTS AGAINST Plutella xylostella AND Crocidolomia pavonana - Prijono, Djoko; Anggraini, Maya; Maryani, Sri Riski; Surya, Eliana Diana (Universitas Lampung, 2021)
Insecticidal joint action of ternary extract mixtures of four species of tropical plants against Plutella xylostella andCrocidolomia pavonana. The diamondback moth (DBM), Plutella xylostella, and the cabbage head caterpillar (CHC),Crocidolomia pavonana, were two main pests of cruciferous vegetable crops. Among the viable alternative ingredients thatcould be utilized to control those two pests were eco-friendly botanical insecticides. This study was conducted to evaluatethe joint action of ternary extract mixtures of four tropical plant species, i.e. Piper aduncum (Pa), Piper retrofractum (Pr),Sapindus rarak (Sr), and Tephrosia vogelii (Tv), against DBM and CHC. Results of leaf-residue feeding bioassays showedthat based on co-toxicity ratio at both LC 50 and LC levels, ternary mixtures of Pa extract with Sr and Tv extracts at concentrationratios of 1:5:1, 1:5:2, and 2:5:1 indicated synergistic joint action on DBM larvae. A mixture of Pa, Sr and Tv extracts at a ratio of2:5:1 was also synergistic to CHC at both LC level but antagonistic at the LC 95 50 95 and LC 95 levels. This mixture at the 1:5:1 ratio was synergistic on CHC at the LC level whereas at the 1:5:2 ratio was antagonistic to CHC at both LC levels. Furthermore, ternary mixtures of Pr extract with Sr and Tv extracts at the three concentration ratios were synergistic to CHC. Thus, ternary mixtures of Pa or Pr extract with Sr and Tv extracts at appropriate concentration ratios are potential alternatives for the control of DBM and CHC.